1859 Ky. Acts 245 - (:unkn) unknown (My University, 1859)
Ch. 33, An Act to Amend An Act Entitled "An Act to Reduce to One the Several Acts in Relation to the Town of Harrodsburg,§ 23: Prohibited the selling, giving, or loaning of a concealed pistol, dirk, Bowie knife, brass knuckles, slungshot, colt, cane-gun, or other deadly weapon to a "minor, slave, or free negro." Punishable by fine of $50.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES